Synthesis and Antibacterial Evaluation of 5-(E)-[4-(2”,5”-Dioxo-2”,5”-Dihydro-1h-Pyrrol-1-Yl)Phenyl]Diazenyl-2-Methyl-N3-Phenyl-3-Thiophenecarboxamide Analogues - J.D, Habila; O.R.A, Iyun; E.E, Ella; N, Tajuddeen; H, Musa (International Journal of Chemistry and Materials Research, 2015)
A series of thiophene-carboxamide analogues (1a-c) were synthesized by incorporating N-phenylmaleimide and 5-amino-4-substituted-(2,4-dimethylphenyl)-2-methyl-3-thiophenecarboxamide and their structures were assigned by studying their spectral data. The synthesised compounds were tested against Staphylococcus aureus and Escherichia coli using agar-in-well diffusion and broth micro dilution methods. The zone of inhibition values ranged from 20 – 24 mm against the two test organisms for all the compounds tested (1a-c). The result of the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) showed that all the test compounds inhibited and completely killed S. aureus and E. coli at a concentration range of 0.63 – 2.50 µg/mL and .031 – 2.50 µg/mL respectively. The MBC value of compound 1a was the same as that of the standard drug (ciprofloxacin) used on E. coli (0.63 mg/mL) and S. aureus (0.25 µg/mL).